Demographic sensitivity inside the local authorities - Raimondo Cagiano de Azevedo; Enrico Todisco (European Regional Science Association (ERSA), 1998)
The knowledge of the administrated population it is not wll appreciated at local level by the Administrators (Majors, Councillors, Public Servants). The attention is more devoted to political items and the sensitivity for the numbers of the population is very feeble. The paper presents the main results a research made in may Municiplities in some Italian Regions (Toscana, Lazio, Molise, Campania, Puglie, Calabria) during 1996. Different topics were put to the attention of the Administrators and they were asked to quantify different demographic and social phenomena in their own institution. The questions were the relevance they assigned to the different matters, how many times they have discussed of said topics in the council, the general (at national level) importance of each aspect. Only recently some main changes appear: The Regions have experienced important demographic changes deeply affecting the local populations and consequently the Local Powers. This is the case of the experience of a so fst decrease in fertility, or the case of the rapid change of several regions from egigration into immigration areas. Unemployment, the elder survival, the family planning, the education, the youth problems, the immigrated population are some of the questions posed to the interviewees. Quite frequently an incoherent process between the perception and the consequent requested action is standing.
Keywords: 330